Comparison of Anteroposterior Vs. Axial X-rays for Assessing Bone Loss in Recurrent Shoulder Dislocation - Shoaib, Muhammad; Muhammad Nadeem; Khan, Ahmed Mushtaq; Iqbal, Muhammad Nauman; Yasin, Azhar (Indus Journal of Bioscience Research, 2024)
Background: Recurrent shoulder dislocation frequently causes the glenoid and humeral head to gradually lose bone, which decreases joint stability and raises the risk of another dislocation. Treating bone loss accurately is crucial, especially when it comes to surgical procedures. The diagnostic precision of axial and anteroposterior (AP) X-rays in identifying and measuring bone loss in patients with repeated shoulder dislocations was examined in this study. Methods: 30 individuals who experienced recurrent shoulder dislocations had axial and anteroposterior (AP) radiography. The humeral head bone loss was measured in millimeters, whereas the glenoid bone loss was expressed as a percentage of the total glenoid surface area. The images were evaluated by two separate radiologists who determined the images’ sensitivity, specificity, and accuracy for both modalities. The Intraclass Correlation Coefficient (ICC) was utilized to assess inter-observer reliability, and Receiver Operating Characteristic (ROC) curve analysis was employed to assess overall diagnostic performance. Results: The sensitivity of axial X-rays was found to be much higher (85%) than that of AP X-rays (70%; p < 0.05). Additionally, axial X-rays demonstrated higher accuracy (83% vs.68%) and specificity (80% vs. 65%). Using Axial X-rays, the mean glenoid bone loss was 16.5%, whereas using AP X-rays, it was 14.2%. For axial X-rays, the humeral head bone loss was 5.6 mm, but for AP X-rays, it was 4.8 mm. Compared to AP X-rays, the ICC for inter-observer reliability was greater for axial X-rays (0.88 and 0.85). Axial X-rays performed better diagnostically than AP X-rays (AUC = 0.71), according to ROC analysis. However, Gold standard investigation for bone loss in recurrent sholder dislocation is always a CT scan. Conclusion: When it comes to identifying and measuring bone loss in repeated shoulder dislocations, axial X-rays provide better diagnostic accuracy than AP X-rays, which is why they are the preferred imaging modality for preoperative evaluation.